Fifteen-Centimeter Giant Tamoxifen-Associated Endometrial Polyp Presenting With Constipation: A Case Report and Review of the Literature - Sompon Apornvirat; Komsun Suwannarurk (Case Reports in Obstetrics and Gynecology)
Endometrial polyps are benign disorganized growth of endometrial glands and stroma in the uterine cavity. They are associated with subfertility, abnormal uterine bleeding, and tamoxifen use. While most polyps are smaller than 2 cm in size, rare giant polyps can cause concerns over malignancy. We report a case of a 15 cm giant endometrial polyp in a 58-year-old woman with a history of tamoxifen use who presented with an uncommon complaint of constipation. Additionally, a literature review of giant endometrial polyp cases is presented. This case represents the largest reported endometrial polyp to date.